Pengembangan Media Pembelajaran Puisi Dengan Memanfaatkan Aplikasi Powtoon Sebagai Alternatif Pembelajaran Pada Masa Pandemi Covid 19 SMA Negeri 1 Wanasari - Ilham Amin Bahtiar; Prasetyo Yuli Kurniawan; Hany Uswatun Nisa (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to find out (1) the needs of teachers and students for poetry learning media by utilizing the powtoon application as an alternative learning during the pandemic, (2) knowing the drafting of learning media by utilizing the powtoon application as an alternative learning during the pandemic, (3) validation test of poetry learning media by utilizing the powtoon application as an alternative to learning during the pandemic. The method used in this research is research and development (R&D) from Borg and Gall which is adapted to research needs, namely the ADDIE model. This research was conducted at SMA Negeri 1 Wanasari. The type of data collected in this study is descriptive quantitative obtained through a needs questionnaire and a validation test questionnaire as a research instrument. The results of the expert assessment were based on three aspects according to Wahono, namely (1) software aspects 88.2%, (2) learning design aspects 84.5%, (3) visual communication aspects 90.6%. The results from the average of the three aspects used are 87.7% which are categorized as very feasible.